2000
DOI: 10.1192/pb.24.8.290
|View full text |Cite
|
Sign up to set email alerts
|

Community mental health team case-loads and diagnostic case-mix

Abstract: Aims and MethodInformation concerning team staffing, keyworker case-loads, and keyworker diagnostic case-mix was collected from six community mental health teams caring for 1651 patients to establish the clinical burden across teams and professions.ResultsTeam case-loads varied from 427 to 121, an average of 275 patients. Over half the patients were female, and psychotic disorders constituted 44% of the sample. The most common diagnoses were schizophrenia (28.6%) and depression (23.6%). Keyworker case-loads va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 2 publications
2
29
2
1
Order By: Relevance
“…Previous descriptions of the work of CMHTs in the UK have reported diagnoses based upon ongoing caseload (Greenwood et al, 2000;Hunter et al, 2002). Their findings of rates of psychotic disorder of around 40% reflect the primary focus of such services being the management of patients with 'severe mental illness', and are not directly comparable with our study, which describes new referrals rather than ongoing case-load.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous descriptions of the work of CMHTs in the UK have reported diagnoses based upon ongoing caseload (Greenwood et al, 2000;Hunter et al, 2002). Their findings of rates of psychotic disorder of around 40% reflect the primary focus of such services being the management of patients with 'severe mental illness', and are not directly comparable with our study, which describes new referrals rather than ongoing case-load.…”
Section: Discussioncontrasting
confidence: 87%
“…3,22 From an English study it was concluded that the case-loads of community psychiatric nurses and occupational therapists in community mental health teams contained far more patients with REVIEW ARTICLE Koekkoek et al Community care for severe personality disorder 23 In a comparable study, it was social workers and again occupational therapists who treated most people with personality disorder. 24 A possible explanation is that patients with severe personality disorders are treated by the professionals with the lowest threshold for inclusion in their case-load (i.e. nonpsychotherapists).…”
Section: Professionals Providing Community Mental Healthcarementioning
confidence: 99%
“…Total figures for frequency of keyworker contact were higher than those ascertained in a recent audit of patient contacts based on CMHT notes (Greenwood et al, 2000): more than double in the case of contact at least every 3 weeks and contact at least quarterly. This implies that either clients were overestimating the frequency of their contact with keyworkers or there is significant under-recording of contacts by professionals.…”
Section: Cmht Contactmentioning
confidence: 66%